PENGARUH PAMDEMI COVID-19 TERHADAP ASPEK BELAJAR PADA PELAJAR SEKOLAH MENENGAH ATAS DI DKI-JAKARTA - Julian, James; Wahyuni, Fitri; Zuchriadi, Achmad; Ferdyanto, Ferdyanto; Tua, Lomo Mula (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2021)
Changes in behavior and normal habits during the Covid-19 pandemic are a challenge faced by any part of the world. A sudden change in habit will certainly have a very significant impact on some circles such as students. Changes in the learning system that were previously carried out offline and changed suddenly online certainly have an impact on the readiness of students to prepare themselves. This study aims to examine the impact of quantitative changes in learning habits from offline systems to online systems by using questionnaires distributed throughout the capital city of Indonesia, namely DKI Jakarta. All of these studies were carried out comprehensively and massively to obtain valid and actual data. Several analytical methods are used such as validity tests, ANOVA tests, and Likert scale tests which are useful for (1) ensuring all data is in good Validity, (2) analyzing and drawing some conclusions from changes in student behavior during the Covid-19 pandemic. From the results of the study, it was found that 47% of students living in the capital city of Indonesia already understand the dangers of the Covid-19 pandemic, the online learning system that has been carried out can become a new habit as much as 54%, the problem that hinders students during this pandemic is Mager (lazy to move) by 36% and the most popular learning system during the pandemic was online learning together with teachers by 68%. (2) analyze and draw some conclusions from changes in student behavior during the Covid-19 pandemic. From the results of the study, it was found that 47% of students living in the capital city of Indonesia already understand the dangers of the Covid-19 pandemic, the online learning system that has been carried out can become a new habit as much as 54%, the problem that hinders students during this pandemic is Mager (lazy to move) by 36% and the most popular learning system during the pandemic was online learning together with teachers by 68%.  Keywords: Covid-19, new habits, offline, online, students. AbstrakPerubahan perilaku dan kebiasaan normal selama pandemi Covid-19 menjadi suatu tantangan tersendiri yang dihadapi oleh belahan dunia manapun. Perubahan kebiasaan secara mendadak tentu akan berdampak sangat signifikan terhadap beberapa kalangan seperti kalangan pelajar. Perubahan sistem belajar yang sebelumnya dilakukan secara luring dan berubah tiba-tiba secara daring tentu berdampak pada kesiapan pelajar dalam mempersiapkan diri mereka masing-masing. Penelitian ini bertujuan untuk mengkaji dampak perubahan dari kebiasaan belajar yang berubah dari sistem luring menjadi sistem daring secara kuantitatif dengan mengunakan kuisioner yang disebar ke seluruh wilayah ibukota Indonesia, yaitu DKI Jakarta. Semua penelitian ini dilakukan secara komprehensif dan masif guna mendapatkan data yang valid dan aktual.  Beberapa metode analisis digunakan seperti uji validitas, uji ANOVA dan uji skala Likert yang berguna untuk (1) memastikan seluruh data dalam valitidas yang baik, (2) menganalisa dan menarik beberapa kesimpulan dari perubahan perilaku pelajar selama pandemi Covid-19 ini berlangsung. Dari hasil penelitian didapatkan bahwa pelajar yang tinggal di Ibukota Indonesia sebesar 47% sudah memahami bahaya pandemi Covid-19, sistem belajar daring yang telah dilakukan bisa menjadi kebiasaan baru sebanyak 54%, masalah yang menjadi penghambat pelajar selama pandemi ini adalah Mager (malas gerak) sebesar 36% dan sistem belajar yang paling diminati selama pandemi adalah belajar daring bersama-sama dengan guru sebesar 68%.